1993
DOI: 10.1111/j.1527-3466.1993.tb00191.x
|View full text |Cite
|
Sign up to set email alerts
|

OPC‐21268: An Orally Effective, Nonpeptide Vasopressin V1 Antagonist

Abstract: Arginine vasopressin (AVP) is among the strongest vasoconstrictors (mediated by V, receptors) and is also an osmotic and body fluid regulator through renal water reabsorption (mediated by V, receptors). The classification of AVP receptors was originally based on intracellular mechanisms: CAMP-independent (V,) and CAMP-dependent (V,) pathways. The intracellular mechanisms of action of V, receptor was explained by the activation of phospholipase C and the subsequent mobilization of intracellular Ca2+ and activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…31 In preliminary studies, it was reported that orally administered OPC-21268 produced some blockade of AVP-induced vasoconstriction in human forearm vasculature 31a and transiently reduced blood pressure in a patient with diabetic renal failure. 32 OPC-21268, which has recently been reviewed, 33,26 will be a useful tool for studies of AVP physiology and may lead to orally active therapeutic agents.…”
Section: A Avp V 1a Selective Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In preliminary studies, it was reported that orally administered OPC-21268 produced some blockade of AVP-induced vasoconstriction in human forearm vasculature 31a and transiently reduced blood pressure in a patient with diabetic renal failure. 32 OPC-21268, which has recently been reviewed, 33,26 will be a useful tool for studies of AVP physiology and may lead to orally active therapeutic agents.…”
Section: A Avp V 1a Selective Antagonistsmentioning
confidence: 99%
“…26 This nonpeptidyl dihydroquinolinone structure, termed OPC-21268 (Fig. 3), was developed by optimization of a lead molecule found through random screening of several thousand compounds.…”
Section: A Avp V 1a Selective Antagonistsmentioning
confidence: 99%